Prospective Study of Day Case Surgery in Otorhinolaryngology and Head-Neck Surgery Department - Islam, M Saiful; Baul, Uttam Kumar Singha (TAJ: Journal of Teachers Association, 2009)
Day case surgery is feasible, safe and economic. The tremendous success of day care surgery is due to advances in surgical as well as anaesthetic techniques and proper postoperative recovery care. In the period January, 2006 to December, 2006 at Rajshahi Medical College Hospital, a total of 390 were operated of which 109 cases were major and 281 cases were minor surgery 327 cases were performed under local anaesthesia, 42 cases were performed by general anaesthesia and 21 cases were done without anaesthesia. Strict patient selection criteria were adopted. As a result postoperative complication rate was only 4.5%. Two patients required readmission to hospital for the management of complications. The most commonly performed otorhinolaryngological surgery in a day care basis is demonstrated, especially in nasal and aural cases. The scope of day case surgery is very limited in case of throat and neck surgery. doi: 10.3329/taj.v20i1.3084 TAJ 2007; 20(1): 17-23